Effect of ethanolic extract of Pericampylus Dawley rats with high fats diets - Muhammad, Kifayatullah; Mohd Shahim, Mustapha; Jesuraj, Aravinth Vijay; Sengupta, Pinaki; Muhammad Shahid, Khan; ., Kaleemullah (Journal of Coastal Life Medicine Editorial Office, 2017)
Objective: To evaluate the effect of ethanolic extract of Pericampylus glaucus (Lam) Merr (P. glaucus) on biochemical parameters in high fats diets treated rats. Methods: The effect of P. glaucus extract on biochemical parameters was studied in male Sprague Dawley rats. The high-fat diets along with standard normal laboratory rat’s diets were given for a period of 28 days along with ethanolic extract of P. glaucus and standard drug. The standard group was treated with simvastatin at dose of 80 mg/kg and the tested groups were treated with ethanol extract of P. glaucus at 400, 600 and 800 mg/kg daily for 28 days of the experiment. The weight of animals in each group was measured weekly and the effect of extract and standard on serum lipids profile was evaluated at the end of the study. Results: The results showed that the ethanolic extract of P. glaucus at different doses of 400, 600 and 800 mg/kg and standard drug induced a significant reduction in the body weight (P < 0.001), total cholesterol, triglycerides (TG), low density lipoproteins (LDL) and uric acid levels and increase (P < 0.001) in high density lipoproteins (HDL) as compared to untreated hyperlipidemic group. Conclusions: The present work indicates that the ethanolic extract significantly suppressed the biochemical parameters in high fats diet treated animals, suggesting the antihyperlipidemic potential of P. glaucus.